Developing preschoolers' listening comprehension skills in English as a second language through interactive story reading - Lapus, Ma. Milagros (2005)
This research is a single-case study of interactive story reading in classroom setting as an alternative teaching strategy to develop listening comperehension skills among Filipino preschoolers learning English as a second language. Results indicated that interactive story reading enhance the subject pupils' higher listening comprehension and retelling skills but in varying degrees based on their previous experiences with books at home. Pupils with more experience with story books and exposure to oral models of English language possessed better listening behavior and had the most diverse and sophisticated responses. Those pupils also acquired retelling skills faster than those who had limited experience with books and few opportunities for oral interaction in English.